Pan-cancer survey of epithelial–mesenchymal transition markers across The Cancer Genome Atlas - Gibbons, Don L. (Dev Dyn, 2017)
BACKGROUND: While epithelial–mesenchymal transition (EMT) can be readily induced experimentally in cancer cells, the EMT process as manifested in human tumors needs to be better understood. Pan-cancer genomic datasets from The Cancer Genome Atlas (TCGA)—representing over 10,000 patients and 32 distinct cancer types—provide a rich resource for examining correlative patterns involving EMT mediators in the setting of human cancers. RESULTS: Here, we surveyed a 16-gene signature of canonical EMT markers in TCGA pan-cancer cohort. The histology or cell-of-origin of a tumor sample may align more with mesenchymal or epithelial phenotype, and non-cancer as well as cancer cells can contribute to the overall molecular patterns observed within a tumor sample; correlation models involving EMT markers can factor in both of the above variables. EMT-associated genes appear coordinately expressed across all cancers and within each cancer type surveyed. Gene signatures of immune cells correlate highly with EMT marker expression in tumors. In pan-cancer analysis, several EMT-related genes can be significantly associated with worse patient outcome. CONCLUSION: Gene correlates of EMT phenotype in human tumors could include novel mediators of EMT that might be confirmed experimentally, by which TCGA datasets may serve as a platform for discovery in ongoing studies.